Pengaruh Tingkat Pendidikan Terhadap Angka Perceraian Tahun 2020 di Pengadilan Agama Kabupaten Pinrang - Musdalipa, Musdalipa (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2024)
This research discusses the implementation of the Independent Curriculum in an effort to improve the quality of education in Indonesia. The Merdeka Curriculum was introduced as a learning model that gives teachers and students the freedom to develop abilities and skills through a project approach and intracurricular activities. This research aims to explore the experience of implementing the Merdeka Curriculum in several schools, evaluate its impact on the quality of learning, and offer recommendations to improve its effectiveness. The research method used is literature study (Library Research). Research findings show that the Merdeka Curriculum makes a positive contribution to the development of students' skills, understanding of concepts and character values. However, the challenges faced include the readiness of schools to implement this curriculum evenly and the availability of adequate resources. This research provides recommendations for education policy to increase support for schools in implementing the Independent Curriculum effectively, as well as to develop more concrete guidelines and strategies to support quality education in Indonesia.